2014
DOI: 10.4028/www.scientific.net/kem.600.150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Adobe Chemically Stabilized with "Synthetic Termite Saliva"

Abstract: The raw mud brick (adobe) is a millenary technology that awakens a wide interest in ecologic and non-conventional constructions. Some advantages are low cost, thermal comfort and minimum environmental impact. For better use, it is important to improve their mechanical properties. Dynasolo DS-328®is a chemical stabilizer used in soil compression for road paving and it is similar to termite saliva. This composition is based on vegetal oils. It is a high-concentrated liquid product, water soluble, non-toxic, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The second factor is that with the greater addition of STS, the water loss will be faster; therefore, cracks may occur in its drying process, reducing its resistance to compression. Faria et al (2016), using STS with cement in soilcement, obtained a significant increase in the resistance to compression; whereas Corrêa et al (2014b), using only STS in several proportions, obtained small differences in the resistance to compression. This result shows that to improve the compressive strength of the adobes, it is necessary use STS with other stabilizers.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The second factor is that with the greater addition of STS, the water loss will be faster; therefore, cracks may occur in its drying process, reducing its resistance to compression. Faria et al (2016), using STS with cement in soilcement, obtained a significant increase in the resistance to compression; whereas Corrêa et al (2014b), using only STS in several proportions, obtained small differences in the resistance to compression. This result shows that to improve the compressive strength of the adobes, it is necessary use STS with other stabilizers.…”
Section: Resultsmentioning
confidence: 90%
“…There has been some research using STS in adobe. Corrêa et al (2014aCorrêa et al ( , 2014bCorrêa et al ( , 2015, found excellent results in the physical-mechanical properties of adobe, mainly due to the stabilization when the adobe came in contact with water. In soil-cement, Faria et al (2016) found satisfactory results using STS.…”
Section: Introductionmentioning
confidence: 98%